THE INFLUENCE OF WORK MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PRODUCTIVITY: AN EMPIRICAL STUDY OF MICRO AND SMALL ENTERPRISES - Alfa Ridho, Syeikhu; Rahma Windayati, Della (Jurnal Manajemen Bisnis dan Terapan, 2025)
Employee productivity plays a vital role in the success of micro and small enterprises (MSEs), especially in labor-intensive sectors such as mushroom cultivation. This study aims to examine the influence of work motivation and work environment on employee productivity within the context of MSEs. A quantitative approach was employed, involving 57 employees selected through a saturated sampling technique. Data were collected using structured questionnaires and analyzed through multiple linear regression, along with classical assumption tests and coefficient of determination analysis. The findings reveal that both work motivation and work environment have a significant and positive effect on employee productivity. The coefficient of determination (R²) value of 81.1% indicates a strong explanatory power of these two internal factors. These results underscore the importance of enhancing intrinsic motivation through recognition and career development, while also fostering a conducive physical and psychological work environment. By addressing these factors simultaneously, organizations can promote sustainable improvements in employee performance. This study contributes to the growing body of literature on human resource management in MSEs and highlights practical strategies for workforce development. However, the study is limited to a single enterprise within the mushroom cultivation sector and focuses only on two internal variables, suggesting the need for further research incorporating additional organizational and individual factors across varied business contexts.